Exploratory Research Study of School Bullying in Medellin - González Rodríguez, Viviana; Mariaca Patiño, Jorge Iván; Arias Tobón, Jacinta Lucía (Pensando Psicología, 2014)
This is an exploratory research study into school bullying among students in Medellin. To carry out the study, 3,373 virtual surveys were conducted across 36 secondary education centers, and this data was used to identify the presence of bullying and the specific forms it takes, according to variables such as age, gender and school grade. The results show that 37.6% of students across both sexes and across all school grades have come into contact with bullying, manifested in behavior such as intimidation and verbal, physical and psychological aggression. The most common forms of aggression were verbal and psychological, and these usually occurred in the presence of peers and teachers in the classroom. The main names given to students who engage in bullying are aggressor and abuser.
Keywords: school bullying; aggressor; secondary education centers; students; witness; victim